2021
DOI: 10.1111/1751-7915.13763
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput molecular analyses of microbiomes as a tool to monitor the wellbeing of aquatic environments

Abstract: Aquatic environments are the recipients of many sources of environmental stress that trigger both local and global changes. To evaluate the associated risks to organisms and ecosystems more sensitive and accurate strategies are required. The analysis of the microbiome is one of the most promising candidates for environmental diagnosis of aquatic systems. Culture-independent interconnected meta-omic approaches are being increasing used to fill the gaps that classical microbial approaches cannot resolve. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 148 publications
(237 reference statements)
1
13
0
Order By: Relevance
“…Changes in the L. vannamei microbiome structure were observed in different stages of development, not only in the varying number of taxons but also in their proportion, which agrees with previous reports [2,3,10,39]. The changes in the microbiome are influenced by intrinsic factors of the host organism, environmental factors, lifestyle and nutrition [46,47]; due to the response capacity the microbiome composition is considered a reliable indicator for external changes. In this aspect the culture conditions of the aquaculture systems can promote the biomass formation of certain microbial groups [9,10,15,21].…”
Section: Taxonomic Composition Of the Active Microbial Communities In...supporting
confidence: 88%
See 2 more Smart Citations
“…Changes in the L. vannamei microbiome structure were observed in different stages of development, not only in the varying number of taxons but also in their proportion, which agrees with previous reports [2,3,10,39]. The changes in the microbiome are influenced by intrinsic factors of the host organism, environmental factors, lifestyle and nutrition [46,47]; due to the response capacity the microbiome composition is considered a reliable indicator for external changes. In this aspect the culture conditions of the aquaculture systems can promote the biomass formation of certain microbial groups [9,10,15,21].…”
Section: Taxonomic Composition Of the Active Microbial Communities In...supporting
confidence: 88%
“…A low transcript representation could be noted in the host and the microbiome of metabolic processes related to "Transport and Catabolism", "Posttranslational modification, protein turnover and chaperones" and "Signal transduction". Previous studies performed in different species have shown that a high representation of these metabolic processes is found in environmental stress conditions [32,40,55,56], the presence of chaperones and chaperonins have particularly been reported previously as stress markers given that their content increases under stress conditions [47]. The low proportion of these metabolic groups in L. vannamei and the microbiome suggests that the environmental variations during the culture of this species were present in a basal state which is common in non-stressed organisms.…”
Section: Functional Characterization Of L Vannamei and Its Microbiome...mentioning
confidence: 88%
See 1 more Smart Citation
“…Microbial communities are an essential link in the lotic trophic chain. They are both shaped by the environment in which they live and, in turn, they shape their environment [148]. Our knowledge of the diversity of microorganisms in sediments from rivers is relatively limited for Romania.…”
Section: Discussionmentioning
confidence: 99%
“…The bio-ecological roles of the main identified taxa are diverse and complex, for example: Proteobacteria offer extreme metabolic diversity [148]; Actinobacteria play an essential role of recycling biomaterials by decomposing complex mixtures of polymers in dead plants and animals and fungal materials and in producing important bioactive natural metabolites [149]. The Firmicutes importance rely on their characteristic as biofertilizers, biocontrol agents, metals uptake enhancers [150] Chloroflexi provide the filamentous scaffolding around which flocs are formed, to feed on the debris from lysed bacterial cells, to ferment carbohydrates and to degrade other complex polymeric organic compounds to low molecular weight substrates to support their growth and that of other bacterial populations; also remove nitrogen and phosphorus [151], etc.…”
Section: Discussionmentioning
confidence: 99%